Bond Strength Survival of a Novel Calcium Phosphate-Enriched Orthodontic Self-Etching System after Various Ageing Protocols: An In Vitro Study - Noor M. H. Garma; Ali I. Ibrahim (Hindawi Limited, 2022)
Objective. This study aimed to evaluate the orthodontic bond strength and enamel-preserving ability of a hydroxyapatite nanoparticles-containingself-etch system following exposure to various ageing methods. Materials and Methods. Hydroxyapatite nanoparticles (nHAp) were incorporated into an orthodontic self-etch primer (SEP, Transbond™ plus) in three different concentrations (5%, 7%, and 9% wt) and tested versus the plain SEP (control) for shear bond strength (SBS), adhesive remnant index (ARI) scores, and enamel damage in range-finding experiments using premolar teeth. The best-performing formulation was further exposed to the following four artificial ageing methods: initial debonding, 24 h water storage, one-month water storage, and one-month acid challenge. A field-emission scanning electron microscope (FE-SEM) was used to examine the integrity of debonded enamel surfaces and calcium-phosphates (CaPs) reprecipitation. Results. The best-performing formulation (7% nHAp-SEP) resulted in significantly lower SBS (p<0.001) than the control SEP following the four artificial ageing methods. Nevertheless, it survived the ageing protocols and yielded clinically acceptable SBS with the advantages of leaving minimal adhesive residue, preserving enamel integrity and smoothness, and inducing CaP reprecipitation as confirmed by FE-SEM images. Conclusions. A newly developed SEP produced adequate orthodontic bond strengths and left unblemished debonded enamel surfaces with minimal remnant adhesive and remineralisation potential, thereby suggesting simpler and safer bonding/debonding procedures.